2007
DOI: 10.1161/strokeaha.107.487108
|View full text |Cite
|
Sign up to set email alerts
|

Protein Aggregation and Proteasome Dysfunction After Brain Ischemia

Abstract: Background and Purpose-Protein unfolding and aggregation are dominant early pathogenic events in neurons after brain ischemia. This study used a transient cerebral ischemia model to investigate whether overproduction of unfolded proteins after brain ischemia is a consequence of proteasome dysfunction. Methods-Proteasome peptidase activity and proteasome subcellular redistribution and assembly were studied by peptidase activity assay, Western blot analysis, and size-exclusion chromatography. Results-Proteasome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(97 citation statements)
references
References 21 publications
(38 reference statements)
6
90
0
1
Order By: Relevance
“…10 It has been suggested that irreversible aggregation of translational complex components, chaperones, and protein folding enzymes following brain ischemia lead to inhibition of translation and subsequent neuron death. 26 Consistent with this view, we detected augmented levels of ubiquitinated proteins after either OGD followed by 24 hr of reperfusion or GBI followed by 3 hr of reperfusion, particularly among high molecular weight protein bands in western blots. This is corrected upon rAAV8-733-CHIP treatment in the hippocampus, thus suggesting that increased E3 ligase activity promoted by CHIP overexpression is sufficient to decrease protein ubiquitination and neuronal degeneration in ischemic conditions.…”
Section: Discussionsupporting
confidence: 85%
“…10 It has been suggested that irreversible aggregation of translational complex components, chaperones, and protein folding enzymes following brain ischemia lead to inhibition of translation and subsequent neuron death. 26 Consistent with this view, we detected augmented levels of ubiquitinated proteins after either OGD followed by 24 hr of reperfusion or GBI followed by 3 hr of reperfusion, particularly among high molecular weight protein bands in western blots. This is corrected upon rAAV8-733-CHIP treatment in the hippocampus, thus suggesting that increased E3 ligase activity promoted by CHIP overexpression is sufficient to decrease protein ubiquitination and neuronal degeneration in ischemic conditions.…”
Section: Discussionsupporting
confidence: 85%
“…Transient cerebral ischemia is associated with an inflammatory response and a rapid and excessive production of various misfolded proteins due to oxidative stress and other mechanisms (Ge et al, 2007. Overproduction of damaged proteins following ischemia is reflected in a pronounced increase of conjugation of targeted proteins with ubiquitin (Hayashi et al, 1992).…”
Section: Ups In Ischemic Conditionsmentioning
confidence: 99%
“…In fact, translational complex components are irreversibly clumped into large abnormal protein aggregates after transient brain ischemia (Liu et al, 2005) or focal brain ischemia (Zhang et al, 2006a), suggesting that the irreversible inhibition of translation in neurons destined to die after ischemia is caused by irreversible aggregation of translational complex components, chaperones and protein folding enzymes. Moreover, proteasomes, particularly the 19S RP, are also sequestered into these protein aggregates in post-ischemic brains (Ge et al, 2007). Furthermore, cytoplasmic ubiquitin-containing aggregates and stress granules are clustered together in CA1 neurons at day 2-3 of reperfusion following global forebrain ischemia and may contribute to sustained translation arrest and CA1 pyramidal neuron vulnerability .…”
Section: Ups and In Vivo Ischemia Modelsmentioning
confidence: 99%
“…1 Animal experiments have demonstrated that many factors are involved in the pathological course of cerebral damage caused by ischaemia and reperfusion, such as endoplasmic reticulum stress and protein aggregation. 2,3 Antioxidants have been shown to have therapeutic effects on ischaemia/reperfusion brain injury, suggesting that oxidative stress has an active role in modulating neuronal destiny. [4][5][6] In addition, other neurological disorders (including neurodegenerative diseases and traumatic brain injury) are related to oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21] This protection is not only associated with inhibition of inflammation and apoptosis, 22,23 but also with attenuation of oxidative stress. 3,24 The aim of the present study was to use a rat model of ischaemia/ reperfusion injury to evaluate the effects of ischaemic postconditioning on mitochondrial ROS production, in order to determine whether its inhibitory effects on oxidative stress are mediated via the mitochondrial pathway, since the golgi apparatus is also a source of ROS. 25 …”
Section: Introductionmentioning
confidence: 99%